Grammatical Errors in Indonesian University Students’ Posters in Yogyakarta - Adila Salma Khansa; Adi Sutrisno (Lexicon, 2019)
This study aims to investigate grammatical errors in posters published byIndonesianUniversitystudents’ inYogyakarta. The errors are classified based on the Surface Strategy Taxonomy by Dulay, Burt, and Krashen (1982) mixed with linguistic categories. Based on the data analysis on 97 posters from 7 universities inYogyakarta, there are 201 errors found. The highest frequency of errors is Omission in terms of number with 122 occurrences (60.69 %), followed by Omission in subject-verb concord with 45 errors (22.38 %), and Omission of preposition with 6 occurrences (2.98 %). In total there are 182 (90.56%) Omission errors, while the other errors only occur less than 10%. The result shows that there are tendencies to omit necessary items rather than add, misform, misorder, or misuse items.